Stakeholders’ Participation in the Creative Economic Development of Cirebon City - Pusparani, Indah Gilang; Kartono, Kartono; Hermawan, Kurnia Tri; Wibowo, Toni Ari (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
This study aims to examine the participation level of stakeholders, identify the dominant stakeholders, and investigate the factors inhibiting stakeholders’ participation in the planning, implementation, and evaluation of creative economic development in Cirebon City. “Creative City” is politically and legally stipulated as the city vision in the regional mid-term development plan 2018-2023 of Cirebon City. As the creative economy is centered around the production, exchanges, and consumption of goods and services from human creativity, Cirebon City is, therefore, a significant case study to investigate how the local government implements participatory processes in developing a creative city.Using qualitative methods, data were collected through a semi-guided interview of 190 respondents from five stakeholders: academics, businesses, communities, government institutions, and media organizations. It was followed by a focus group discussion of 12 key respondents selected purposively from the five stakeholders. With primary and secondary data sources, qualitative data was analyzed through the process of data reduction, data display, and conclusion drawing/verification.This study concluded that stakeholders' participation in all stages of creative economic development in Cirebon was still minimal. The businesses in culinary subsectors as the most dominant stakeholders in the participation processes. The lack of socialization from the municipal government and the limited collaboration amongst the stakeholders were identified as the inhibiting factors of inclusive participation in creative city development. The government needs to accelerate creative economic development through multisectoral policies, including improvement of business knowledge and skills of the local business actors, goods and services’ quality upgrading and assurance, certification and legal assistance, as well as promotion and market expansion